Improving social understanding of individuals of intellectual and developmental disabilities through a 3D-facail expression intervention program - Cheng, Yufang; Chen, Shuhui (Research in developmental disabilities, 2010)
Individuals with intellectual and developmental disabilities (IDD) have specific difficulties in cognitive social-emotional capability, which affect numerous aspects of social competence. This study evaluated the learning effects of using 3D-emotion system intervention program for individuals with IDD in learning socially based-emotions capability in social contexts. The 3D-emotion system involves three stages with 24 questions with designed different social events. The experimental study was to evaluate using a single subject design on three participants with IDD for identifying the effects of 3D-emotion system intervention program; and the collected data of using this system and informal interview with the participants’ were involved. The results showed that three participants had significant positive effects on using of the 3D-emotion system intervention program, and in terms of follow-up learning have been discussed in this paper.